2018
DOI: 10.1080/87565641.2018.1485679
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Amygdala in Memory and Psychosocial Functioning in Pediatric-Onset Multiple Sclerosis

Abstract: Youth with multiple sclerosis (MS) often experience cognitive impairment and psychosocial disturbances. We describe the relationship between memory function, psychosocial skills, and brain volume in 32 patients with pediatric-onset MS and 30 controls. Amygdala volume was significantly lower in patients compared with controls. In general, poorer memory was associated with reduced functional communication skills and reduced amygdala volume. Greater amygdala volume in patients correlated with parent-reported func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…We found that patients with POMS demonstrated reduced accuracy on a test of verbal recognition (i.e., word list) and were slower to recognize faces that were recently presented. Consistent with previous imaging research in POMS ( Fuentes et al, 2012 , Green et al, 2018 , Kerbrat et al, 2012 , Mesaros et al, 2008 , Till et al, 2011 ), we also found that patients with POMS showed smaller normalized thalamic volume compared to HCs and this effect was most robust relative to other brain regions examined in our study. Difficulty with verbal recognition is consistent with prior POMS studies that evaluated episodic memory using word list recall ( Amato et al, 2008 , Fuentes et al, 2012 , MacAllister et al, 2005 , MacAllister et al, 2007a , Smerbeck et al, 2011 , Till et al, 2013 ), suggesting a deficit at the encoding stage for verbal information.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that patients with POMS demonstrated reduced accuracy on a test of verbal recognition (i.e., word list) and were slower to recognize faces that were recently presented. Consistent with previous imaging research in POMS ( Fuentes et al, 2012 , Green et al, 2018 , Kerbrat et al, 2012 , Mesaros et al, 2008 , Till et al, 2011 ), we also found that patients with POMS showed smaller normalized thalamic volume compared to HCs and this effect was most robust relative to other brain regions examined in our study. Difficulty with verbal recognition is consistent with prior POMS studies that evaluated episodic memory using word list recall ( Amato et al, 2008 , Fuentes et al, 2012 , MacAllister et al, 2005 , MacAllister et al, 2007a , Smerbeck et al, 2011 , Till et al, 2013 ), suggesting a deficit at the encoding stage for verbal information.…”
Section: Discussionsupporting
confidence: 93%
“…Still, the group-level differences showed small-to-moderate effect sizes (Cohen’s d ranging from 0 to 0.57). These findings lead us to question whether and how these differences may be experienced in day-to-day life such as in academic, occupational, and social spheres at the individual level and how to examine this in future work (e.g., Green et al, 2018 , MacAllister et al, 2007b , Till et al, 2012 ). Though depression and anxiety can influence cognitive performance in MS including memory and emotion identification ( Leavitt et al, 2020 , Ziccardi et al, 2021 ), our sample of POMS participants did not report greater emotional distress relative to HCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, grey matter (GM) atrophy showed greater correlations with cognitive outcomes, and even more specifically, findings of thalamic atrophy were associated with neurocognitive status. Volume reduction at the onset in POMS with further reduction over time is similar to adult findings and concerning when considering neurocognitive outcomes [31,79,80,81,82,83,84,85,86,87,88,89,90].…”
Section: Disease Characteristics Associated With Cognitive and Psysupporting
confidence: 66%
“…Global hippocampal volume did not differentiate between intact and cognitive impaired patients; however, particular regions of the hippocampus (subiculum, dentate gyrus subfields of right hippocampus) were different between these groups [87]. Another group [88] found that amygdala volume was smaller in patients compared to controls and poorer memory was associated with reduced amygdala volume. Amygdala volume was also associated with parent-reported adaptive skills (social skills, communication).…”
Section: Disease Characteristics Associated With Cognitive and Psymentioning
confidence: 99%